Impact of the Asian gall wasp Dryocosmus kuriphilus on the radial growth of the European chestnut Castanea sativa. Issue 6 (14th March 2021) - Marcolin, Enrico; Pividori, Mario; Colombari, Fernanda; Manetti, Maria Chiara; Pelleri, Francesco; Conedera, Marco; Gehring, Eric
Abstract: The invasion of the Asian chestnut gall wasp Dryocosmus kuriphilus (ACGW) in Europe has caused serious biological and economic impacts on chestnut stands that have been partially solved with the introduction of the biological control agent Torymus sinensis . However, information concerning tree‐ring growth during the ACGW epidemic has been lacking so far. Using dendrochronology techniques, we analysed the impact of the ACGW on tree‐ring growth and the capacity of the chestnut tree to recover when biocontrol was achieved in seven sites covering the area of first detection and subsequent spread of the ACGW in Europe. In each site, a non‐target control species (i.e. trees not attacked by the ACGW) has been included as a reference in the analysis. Results show a reduction in the tree‐ring increment by 60% on average during the ACGW epidemic. Such effects were higher in the magnitude and longer in the duration when compared to other stresses such as insect defoliation or extreme summer droughts. Synthesis and applications . Marked reductions in radial growth were evident in the years of ACGW attack regardless of the age of the chestnut coppices. Since most of the trees only recovered to an almost normal growth rate after 3–4 years of biocontrol by T. sinensis, an immediate release of the antagonist at the first ACGW appearance is highly recommended. The consequences and perspectives of ACGW's attacks on the quality of the timber produced are also discussed. Abstract : Marked reductions in radial growth were evident in the years of ACGW attack regardless of the age of the chestnut coppices. Since most of the trees only recovered to an almost normal growth rate after 3–4 years of biocontrol by T. sinensis, an immediate release of the antagonist at the first ACGW appearance is highly recommended. The consequences and perspectives of ACGW's attacks on the quality of the timber produced are also discussed.